2010
DOI: 10.1073/pnas.1005198107
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione import in Haemophilus influenzae Rd is primed by the periplasmic heme-binding protein HbpA

Abstract: Glutathione (GSH) is a vital intracellular cysteine-containing tripeptide across all kingdoms of life and assumes a plethora of cellular roles. Such pleiotropic behavior relies on a finely tuned spatiotemporal distribution of glutathione and its conjugates, which is not only controlled by synthesis and breakdown, but also by transport. Here, we show that import of glutathione in the obligate human pathogen Haemophilus influenzae , a glutathione auxotrophe, is mediated by the ATP-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 45 publications
2
108
0
Order By: Relevance
“…These periplasmic binding proteins share homology and structural characteristics with SapA. Preliminary titration experiments of SapA-heme complexes resolved by native PAGE revealed that the K D of heme association with SapA was greater than 50 M, similar to that described for the DppA-heme and HbpA-heme complexes (19,47). Further, SapA-heme complexes were detected using isothermal titration calorimetry.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…These periplasmic binding proteins share homology and structural characteristics with SapA. Preliminary titration experiments of SapA-heme complexes resolved by native PAGE revealed that the K D of heme association with SapA was greater than 50 M, similar to that described for the DppA-heme and HbpA-heme complexes (19,47). Further, SapA-heme complexes were detected using isothermal titration calorimetry.…”
Section: Resultsmentioning
confidence: 62%
“…The biochemical properties of heme and the low affinity for complex formation make the use of standard methodologies ineffective in the elucidation of precise dissociation constants (47). Despite these limitations, we attempted to estimate the relative affinity of heme for SapA by various methods previously used to determine the heme-binding affinities of the dipeptide and heme-binding proteins DppA and HbpA (19,47).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used this property of hemin to demonstrate the characteristics of hemin binding to PE using a UV-visible spectrophotometer (Vergauwen et al, 2010). Purified PE (15 μM) was incubated with 30 μM hemin in TS buffer for 1 h at room temperature and samples were scanned between 300 nm to 600 nm by using a UV-visible spectrophotometer.…”
Section: Uv-visible Spectrophotometry and Pe-hemin Binding Analysismentioning
confidence: 99%